2017
DOI: 10.1021/acsami.7b05912
|View full text |Cite
|
Sign up to set email alerts
|

Surface PEG Grafting Density Determines Magnetic Relaxation Properties of Gd-Loaded Porous Nanoparticles for MR Imaging Applications

Abstract: Surface PEGylation of nanoparticles designed for biomedical applications is a common and straightforward way to stabilize the materials for in vivo administration and to increase their circulation time. This strategy becomes less trivial when MRI active porous nanomaterials are concerned as their function relies on water/proton-exchange between the pores and bulk water. Here we present a comprehensive study on the effects of PEGylation on the relaxometric properties of nanozeolite LTL (dimensions of 20 × 40 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The contour length (full extended length) is calculated as a product of the polymeric length (N) and length of the monomeric unit, 3.5 Å for PEG. 54 …”
Section: Resultsmentioning
confidence: 99%
“…The contour length (full extended length) is calculated as a product of the polymeric length (N) and length of the monomeric unit, 3.5 Å for PEG. 54 …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1, the small leakage of Gd III ions from Zr(oxalate)/Gd III -LTL and Zr(chloride)/Gd III -LTL nanoparticles in both media could be reduced upon PEGylation of their surface, as reported earlier for Gd III -LTL. 19 The leakage of Zr IV ions follows the same trend in PBS, while in serum, the difference between the two Zr-loading procedures becomes apparent for the non-PEGylated Zr(oxalate)/Gd III -LTL and Zr(chloride)/Gd III -LTL nanoparticles with 4.2 and 1.6 wt % released Zr IV ions, respectively. This moderate leakage indicates a strong binding of this tetravalent metal-ion to the LTL framework, whether on the surface or in the inner pores.…”
Section: Stability and Functionalmentioning
confidence: 83%
“…Surface functionalization of nanoparticles is a common way to stabilize them prior to in vivo applications. In our previous study, we have shown that this strategy not only provides the nanoparticles with the necessary colloidal stability but also prevents the leakage of toxic ions loaded in the porous LTL crystals . Thus, in the current study, the PEGylation step was adapted to the radiolabeling procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, the relaxivity of Gd 2 Hf 2 O 7 @PDA@PEG-Pt-RGD NPs slightly enhanced to 38.28 mM –1 s –1 . It may be due to the fact that the PDA on the surface of MRI CA confines water molecules in the CA’s vicinity and then enhances the r 1 value. ,, Furthermore, Gd 2 Hf 2 O 7 and Gd 2 Hf 2 O 7 @PDA@PEG-Pt-RGD NPs provide considerably brighter images than Magnevist. It is demonstrated that Gd 2 Hf 2 O 7 @PDA@PEG-Pt-RGD NPs with higher relaxivity can obtain brighter images (Figure b), which is favorable for guiding tumor therapy.…”
Section: Resultsmentioning
confidence: 99%